(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
In this essay, our objective is to explore the impact of the myths of racial democracy and racial harmony on society, emphasizing the gap between these conceptions and reality. The methodology employed involves a bibliographic approach and critical analyses, primarily of the works of Lélia Gonzales and Virgínia Bicudo. Gonzales provides insights into the influence of language in shaping racial identity, while Bicudo highlights the presence of concealed racism in Brazilian society. Both authors utilize psychoanalysis as a foundation for comprehending the social and historical contradictions in Latin America. The conclusions point to the notion that a critical understanding of the concepts of democracy and racial harmony in contemporary society can only be achieved through a thorough historical and psychoanalytic analysis.